2021
DOI: 10.1002/onco.13722
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Ovarian Escape in Premenopausal Estrogen Receptor-Positive Breast Cancer Patients on Ovarian Suppression Therapy

Abstract: Purpose. To evaluate the proportion of premenopausal women who experience persistent ovarian escape (OE) while receiving ovarian suppression (OS) therapy for estrogen receptor positive (ER+) breast cancer treatment. The study also examines clinical factors that may predispose to higher risk of persistent OE. Methods/Materials. This was a retrospective, "real-world" study to evaluate premenopausal women receiving adjuvant endocrine OS therapy. The primary objective was to measure the percentage of persistent OE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This patient was 35 years old at the time of diagnosis and had a BMI between 22.7 and 23.4 kg/m 2 during the follow-up period. In several studies on OFS, ovarian escape cases were observed during OFS administration (28,30); however, to our knowledge, to date, no considerable results have shown the prognostic significance of ovarian escape, and currently, there is no guideline for such cases. Accordingly, careful follow-up and further investigations are needed for ovarian escape cases.…”
Section: Discussionmentioning
confidence: 95%
“…This patient was 35 years old at the time of diagnosis and had a BMI between 22.7 and 23.4 kg/m 2 during the follow-up period. In several studies on OFS, ovarian escape cases were observed during OFS administration (28,30); however, to our knowledge, to date, no considerable results have shown the prognostic significance of ovarian escape, and currently, there is no guideline for such cases. Accordingly, careful follow-up and further investigations are needed for ovarian escape cases.…”
Section: Discussionmentioning
confidence: 95%
“…Since efficacy data in premenopausal women became available ( 4 , 5 ), fulvestrant (with GnRH for ovarian suppression) in combination with CDK4/6 or in monotherapy is a widely used option in ABC premenopausal women ER+. Failure to attain complete ovarian suppression with GnRH can however occur ( 7 , 8 ) and may conceivably be associated with higher recurrence risk ( 9 , 10 ). So, although not a level I recommendation, routine monitorization of estradiol in these patients may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The reference interval for considering post-menopausal females cutoff is <32.2 pg/mL ( 16 ). The definition for complete ovarian suppression while on a GnRH agonist is not clearly defined ( 8 ). We used the estradiol cut-off levels for naturally postmenopausal women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young age was associated with a higher chance of developing ovarian escape. 15 Chlebowski et al 16 conducted a meta-analysis and concluded that given the discordance between DFS and OS and inconsistent estrogen suppression with OFS plus aromatase inhibitor, it is premature to be recommended as a routine approach for premenopausal woman. As a result, in premenopausal women on OFS, estrogen levels should still be checked if aromatase inhibitors are used rather than tamoxifen.…”
Section: The Optimal Agent To Pair With Ofsmentioning
confidence: 99%